Casos notificados de sífilis em gestantes na área da Estratégia da Saúde da Família da Marambaia nos anos de 2021 a 2022 - SANTOS, Naldinei Diniz dos (2024)
Syphilis is a sexually transmitted, infectious and contagious infection, transmitted by the bacterium Treponema pallidum, which, when acquired during pregnancy, can lead to miscarriage, fetal or neonatal death, prematurity and serious damage to the health of the conceptus, such as ophthalmological impairment, auditory, bone and neurological. In Brazil since 2005, cases of pregnant and congenital syphilis have increased, which demonstrates the urgency of a prevention and control system for these indicators. In this context, the study aims to investigate the number of cases of Syphilis in pregnant women in the area of the Family Health Strategy of Marambaia - ESF, in the period 2021 and 2022, as well as to draw a profile of this population. The research took place in the municipality of Curralinho from September to October 2022, data collection took place through the files and medical records of patients from the Family Health Strategy Health Unit of Marambaia. 07 pregnant patients diagnosed with syphilis were analyzed, with 01 case registered in 2021 and 06 in 2022, representing a significant increase close to 86%. With regard to the profile, they are all brown, aged between 15 and 29 years, most students with incomplete high school.